MicroRNAs in Obesity, Metabolic Syndrome and Diabetes Mellitus - Anna Meiliana; Andi Wijaya (The Indonesian Biomedical Journal, 2011)
BACKGROUND: MicroRNAs (miRNAs) are small regulatory RNAs that play important roles in development of diseases. Several studies have provided evidences showing that miRNAs affect pathways that are fundamental for metabolic control in adipocyte and skeletal muscle differentiations. Some miRNAs have been implicated in lipid, amino acid, and glucose homeostasis. This leads to the possibility that miRNAs may contribute to common metabolic diseases and point to novel therapeutic opportunities based on targeting of miRNAs.CONTENT: miRNAs have been recognized as a class of epigenetic regulators of metabolism and energy homeostasis, primarily because the simultaneous regulation of a large number of target genes can be accomplished by a single miRNA. Emerging evidences suggest that miRNAs play a key role in the pathological development of obesity by affecting adipocyte differentiation. miRNAs have been implicated as novel protagonists in the pathogenesis of Diabetes Mellitus (DM), regulation of insulin production, secretion and action. They also appear to play a role in the development of diabetic complications such as nephropathy and cardiac hypertrophy.SUMMARY: Involvement of miRNAs in glucose and lipid metabolism has provided strong evidences to confirm their roles as key players in regulation of complex metabolic pathways. Additionally, it indicates potential outlook for novel therapeutic strategies in the management of obesity, metabolic syndrome and DM. Further research in this field is needed to ascertain the full potential of miRNAs as novel metabolic biomarkers and potent therapeutic agents against obesity and its metabolic disorders.KEYWORDS: obesity, metabolic syndrome, diabetes, miRNAs, adipogenesis, insulin, pancreatic cells